Peran Pembelajaran Daring, Komunikasi, Dan System E-Learning Terhadap Motivasi Belajar Mahasiswa - Achmad Rizky Fambudianto; Sofia Amriza, Rona Nisa; Ardianing Kusuma, Dwi Januarita (AI Society & STMIK Indonesia, 2022)
Online learning is the main learning system amid government policies that have closed face-to-face learning activities as a result of the emergence of Covid-19. Based on pre-study data, it shows that the obstacles that interfere with the learning process are learning content that is less attractive, internet networks that are less supportive, and inadequate digital devices. In the communication aspect, problems that arise, such as students who cannot ask questions directly to lecturers, and online learning which is not as interactive as face-to-face learning. Meanwhile, from the aspect of the E-Learning System, the problems that arise are the content, content, or appearance that is less attractive and interactive, information that is not optimal, not up-to-date, and E-Learning is less stable. This research was conducted to analyze the role of online learning, communication, and E-Learning systems on learning motivation. The approach is carried out using quantitative methods and processed using Structural Equation Modeling Partial Least Squares (SEM-PLS). As a result, it was found that the facilities and knowledge of the teacher had a significant positive effect on students' learning motivation with p-values ​​of 0.00.